Comparison of Triage Revised Score and CRAMS Scale as predictors of outcome for adult trauma patient in Emergency Department, Hospital Universiti Sains Malaysia - Ani, Noor Hafiza Che (2017)
INTRODUCTION: Trauma is an important health problem and a leading cause of death among young adults. Early recognition of injury severity could aid in managing trauma patient. Triage scores that capable to predict outcome would give better assessment of patient urgency to get proper treatment at trauma center. OBJECTIVE: To compare the utility of Triage Revised Trauma Score (T-RTS) with CRAMS Scale in determining outcome of adult trauma patient in Emergency Department (ED), Hospital Universiti Sains Malaysia (HUSM). METHODS: A Prospective cohort study that was conducted within three months study period from December 2015 until February 2016 by assessing adult trauma patients at triage and their disposition from ED. RESULT: 91 patients were recruited. For T-RTS, 12 patients (13.2%) were score as major, and 79 patients (86.8%) were scored as minor (median=12, IQR=0). For CRAMS, 10 patients (11.0%) were scored as major, and 81 patients (89.0%) were scored as minor (median-=10, IQR=1). T-RTS sensitivity is 71.4% while CRAMS Scale sensitivity is 72.4 %. CRAMS score have higher specificity 94.0% compare to T-RTS specificity 91.7%. Both scoring system have high negative predictive value, 97.5%. CRAMS Scale had higher positive predictive value compared to T-RTS (50.0% and 41.7% respectively). CONCLUSION: Our study showed CRAMS Scale was better than T-RTS in predicting patient outcome from ED. Further study needed to be done with larger sample size and longer duration in order to improve the reliability of the study.